2013
DOI: 10.1016/j.immuni.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2-5+Islet1+ Mesenchymal Precursors Generate Distinct Spleen Stromal Cell Subsets and Participate in Restoring Stromal Network Integrity

Abstract: Lymphoid organ stromal cells comprise different subsets whose origin remains unknown. Herein, we exploit a genetic lineage-tracing approach to show that splenic fibroblastic reticular cells (FRCs), follicular dendritic cells (FDCs), marginal reticular cells (MRCs), and mural cells, but not endothelial cells, originated from embryonic mesenchymal progenitors of the Nkx2-5+Islet1+ lineage. This lineage included embryonic mesenchymal cells with lymphoid tissue organizer (LTo) activity capable of supporting ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 46 publications
10
87
1
Order By: Relevance
“…The spleens of DTX-treated DM2 mice did not differ from those of littermate controls (Fig. 2B), in accordance with the splenic FRC being FAP − and having a different origin from that of LN FRCs (25). Depletion of the FAP + stromal cells resulted in substantial disruption of the gp38 + FRC network throughout the T-cell zone within 1 d of the last DTX treatment, with both the extracellular matrix, as defined by laminin staining, and the localization of the remaining B cells to the follicle being maintained (Fig.…”
Section: Ln Frcssupporting
confidence: 72%
“…The spleens of DTX-treated DM2 mice did not differ from those of littermate controls (Fig. 2B), in accordance with the splenic FRC being FAP − and having a different origin from that of LN FRCs (25). Depletion of the FAP + stromal cells resulted in substantial disruption of the gp38 + FRC network throughout the T-cell zone within 1 d of the last DTX treatment, with both the extracellular matrix, as defined by laminin staining, and the localization of the remaining B cells to the follicle being maintained (Fig.…”
Section: Ln Frcssupporting
confidence: 72%
“…E13.5 WT littermate spleens were divided into 2 groups and cultured, on a collagen layer, in the presence of RA or vehicle. Quantitative analysis of spleen Tlx1 mutant SPM results in premature cellular differentiation, we evaluated the expression of Desmin, a marker associated with maturation of spleen mesenchymal cells (57)(58)(59). Desmin was strongly upregulated at both the mRNA and the protein level in E13.5 Tlx1 mutants as compared with control embryonic spleens ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these observations, we showed that Tlx1 mutant spleens exhibit reduced vasculogenesis and premature differentiation of mesenchymal progenitors. RA mediates these effects, since addition of RA to spleen organotypic cultures reduces Vegf-a expression while inducing Desmin and other markers normally expressed by mature lymphoid stromal cells (59). Also, Tlx1 is not expressed in endothelial cells of the SPM, indicating a non-cell-autonomous role in the vasculogenesis defect.…”
Section: Discussionmentioning
confidence: 99%
“…During embryogenesis, spleen is believed to develop from a mesoderm-derived cell layer, the splanchnic mesodermal plate (26). Splenic stroma, including fibroblastic reticular cells, FDCs, and pericytes, develops directly from embryonic mesenchymal cells (27). Therefore, in LT-deficient mice exhibiting spleen formation, these mesenchymal-derived cell lineages must be capable of driving spleen organogenesis from embryonic through to adultstage tissue independently of LTa 1 b 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic spleen, LTi cluster around CD31 + (25) or VE-cadherin + MAdCAM-1 + vessels (15), which may represent precursors of adult WP (24) or MRCs (28). Such organizer-like cells expressing CD31 would not arise from embryonic mesenchymal cells (27), suggesting the existence of a second endothelial-lineage spleen organizer population. Indeed, LN CD31 + endothelial cells have now been recognized as a critical component for tissue formation in an LTbR-dependent manner (29).…”
Section: Discussionmentioning
confidence: 99%